Extramedullary acute myelogenous leukemia. Issue 5 (September 2016) - Solh, Melhem; Solomon, Scott; Morris, Lawrence; Holland, Kent; Bashey, Asad
Abstract: Extramedullary leukemia (EM AML), also known as myeloid sarcoma, is a rare manifestation of acute myelogenous leukemia and often accompanies bone marrow involvement. EM AML is diagnosed based on H&E stains with ancillary studies including flow cytometry and cytogenetics. Isolated EM AML is often misdiagnosed as large cell lymphoma or other lymphoproliferative disorder. The clinical presentation is often dictated by the mass effect and the location of the tumor. The optimal treatment remains unclear. High-dose chemotherapy, radiation, surgical resection, and allogeneic stem cell transplantation are all modalities that can be incorporated into the therapy of EM AML. Cytarabine-based remission induction regimens have been the most commonly used in the upfront setting. There are limited data about the optimal consolidation. Transplantation is ideally offered for high risk disease or in the relapsed setting. In this manuscript, we will review the recent literature about EM AML, focusing on therapy and proposing a treatment algorithm for managing this rare form of leukemia. Further studies addressing risk stratification, role of molecular and genetic aberrations, and optimal treatment strategies are warranted.